HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU DENGAN PENERAPAN KESELAMATAN DAN KESEHATAN KERJA NELAYAN DI PELABUHAN KOTA AGUNG TAHUN 2024 - Seroja, Estrelitha Maytari; Hasan, Amrul; Trigunarso, Sri Indra (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Occupational Safety and Health (K3) is a field of science related to the health, safety, and welfare of humans working in an institution or project location. The existence of occupational safety and health for workers is very important to anticipate and reduce the number of work accidents and occupational diseases as well as to protect workers, the government issued Law on Manpower No. 13 of 2003 Article 86 Paragraphs 1 and 2 which states "Every worker/laborer has the right to obtain protection for: occupational safety and health; morals and morality; and treatment in accordance with human dignity and religious values".To protect the safety of workers/laborers in order to realize optimal work productivity, occupational safety and health efforts are carried out". Including the work of fishermen, it is also considered necessary to implement occupational safety and health. This study aims to determine the relationship between knowledge, attitudes and behavior with the implementation of occupational safety and health for fishermen at Kota Agung Port in 2024.The research method uses a quantitative approach. The number of samples was 89 fishermen laborers at Kota Agung Port. Data collection was carried out by conducting observations and interviews. The data analysis carried out was univariate and bivariate using the Chi Square test through the SPSS (Statistical Practice Social Science) application. The conclusion of this study is that there is no relationship between knowledge and the implementation of occupational safety and health for fishermen at Kota Agung Port in 2024, p-value = 0.407 or> α-value = 0.05 or not significant. There is no relationship between attitude and the implementation of occupational safety and health for fishermen at Kota Agung Port in 2024, p-value = 1.0 or> α-value = 0.05 or not significant. And there is a relationship between behavior and the implementation of occupational safety and health for fishermen at Kota Agung Port in 2024, p-value = 0.000 or <α-value = 0.05 or significant.